Chapter Ecosistemi, boschi e servizi ecosistemici - Schirone, Bartolomeo (Territori, 2020)
A series of considerations about the value of the living, the difference between natural ecosystems, neo-ecosystems and artificial systems, self-organization and emerging behaviors, the difference between forests managed and intact in the provision of ecosystem services lead to introduce, alongside the latter, the eco-benefit concept. This perspective requires planning on scales having as a reference the water catchment area, a key element in the fractal nature of the landscape, and to consider forest rewilding as an essential step in territorial politics.